Changes in Inflation Persistence Prior and Subsequent to the Subprime Crisis: What are the Implications for South Africa? - Phiri, Andrew (Journal of Reviews on Global Economics, 2017)
The appropriateness of the inflation targeting regime as a policy framework for the South African Reserve Bank (SARB) continues to be a furiously debated topic for both academics and policymakers alike. In this study, we approach this debate by examining whether there have been any changes in the persistence of the inflation process for periods prior and subsequent to the global financial crisis. By effect, our study attempts to answer the question of whether inflation targets have been successful in controlling inflation rates in the face of unanticipated financial crisis. Indeed, our empirical results indicate that persistence in the inflation process has decreased in periods subsequent to the subprime crisis, and yet this has been accompanied by decreases in economic growth and unchanged high levels of unemployment. Our study ultimately suggests that given the current status of the economy, inflation may be required to be lowered to close-to-zero levels which will have to be accompanied with higher levels of economic growth, separate macroeconomic policies which specifically target unemployment and a change in domestic real interest rates.